UTILIZATION OF CULTURAL CAPITAL IN COMMUNITY-BASED TOURISM DEVELOPMENT IN SADE VILLAGE OF CENTRAL LOMBOK - Muh. Hilmi Pauzi; Hasan Basri; Muh. Fahrurrozi; Muhammad Adi Junaidi; Muhammad Ramli; Zaitun Zaitun; Herman Supriadi (STKIP Persada Khatulistiwa Sintang, 2022)
The main issues of this research are: how the cultural capital operated on the field of tourism which the specific influences disposition to the tourism practice model in Sade Village and then how the mechanism of cultural capital to produce the tourism attraction, kind of tourism product and economic capital. The research uses descriptive qualitative with ethnography. Data collection, however, uses field observation, in-depth interviews, and documentation. Data validation employs triangulation, information review, and extension presence. The result showed that the community-based tourism represents the cultural practice of Sade society illustrated cultural capital. Some cultures presented on tourism practice: 1) the habit of traditional cloth making referring to heritage culture of Sade society; 2) the traditional architecture morphology style which was the complex values while it is the product of tourist consumed; and 3) the traditional art fight (presean), traditional music (Gendang Beleq) and new attractions of Amaq Tempungus danced.